Gooseberry (Grossularia reclinata (L.) Mill.) resistance to Septoria leaf spot (Septoria ribis Desm.) in the Western Forest- Steppe of Ukraine - С. І. Градченко; О. П. Лушпіган (Plant Varieties Studying and Protection)
The results obtained during the study of resistance of promising gooseberry varieties to Septoria leaf spot in the Western Forest-Steppe of Ukraine are described. Variety samples were divided into groups by the resistance to disease. Among them none was found with complete field  resistance. Sladkiy proved to be highly resistant variety. Resistance above the average is typical for Berill, Grushenka, Kooperator, Lehin, Malakhit, Rodnik, Shennon varieties. Hrossulyar, Kamenyar, Karat, Knyazhych, Kolobok, Krasnoslavyanskiy, Laskovyi, Mazershkota, Russkiy, Svityaz, Severnyi kapitan are varieties of average resistance to Septoria leaf spot. Zyelyonyi dozhd, Zlatogor, Invikta, Kubanyets, Nesluhivskyi, Slivovyi are characterized as low resistant ones.